Interactions of a bacterial Cu(I)-ATPase with a complex lipid environment - Autzen, H; Koldsø, H; Stansfeld, P; Gourdon, P; Sansom, M; Nissen, P (American Chemical Society, 2018)
Phospholipids and sterols play multiple roles in cells. In addition to establishing barriers between compartments, they also provide the matrix for assembly and function of a large variety of catalytic processes. Lipid composition is a highly regulated feature of biological membranes, yet its implications for membrane proteins are difficult problems to approach. One obstacle is the inherent complexity of observing and describing these interactions and their dynamics at a molecular and atomic level. However, lipid interactions are pivotal for membrane protein function and should be acknowledged. The enzymatic activity of several different P-type ATPases, one of the major families of ion pumping primary active transporters, has previously been shown to exhibit a strong dependence on phospholipids; however, distinguishing the effects of annular and specific lipid interactions is challenging. Here we show that the hydrolytic activity of a bacterial Cu(I)-transporting P-type ATPase (LpCopA) is stimulated by the bacterial, anionic phospholipid cardiolipin and to some extent by phosphatidylglycerol. Furthermore, multiscale molecular dynamics simulations pinpoint lipid hot spots on the membrane-spanning domain of LpCopA. Thus, using two independent methods, our study shows converging evidence that the lipid membrane composition plays an important role for LpCopA.